Physical Localization of the Root-Knot Nematode (Meloidogyne incognita) Resistance Locus Me7 in Pepper (Capsicum annuum) - Changkwian, Amornrat; Venkatesh, Jelli; Lee, Joung-Ho; Han, Ji-Woong; Kwon, Jin-Kyung; Siddique, Muhammad Irfan; Solomon, Abate Mekonnen; Choi, Gyung-Ja; Kim, Eunji; Seo, Yunhee; Kim, Young-Ho; Kang, Byoung-Cheorl (Frontiers in Plant Science, 2019)
The root-knot nematode (RKN) Meloidogyne incognita severely reduces yields of pepper (Capsicum annuum) worldwide. A single dominant locus, Me7, conferring RKN resistance was previously mapped on the long arm of pepper chromosome P9. In the present study, the Me7 locus was fine mapped using an F2 population of 714 plants derived from a cross between the RKN-susceptible parent C. annuum ECW30R and the RKN-resistant parent C. annuum CM334. CM334 exhibits suppressed RKN juvenile movement, suppressed feeding site enlargement and significant reduction in gall formation compared with ECW30R. RKN resistance screening in the F2 population identified 558 resistant and 156 susceptible plants, which fit a 3:1 ratio confirming that this RKN resistance was controlled by a single dominant gene. Using the C. annuum CM334 reference genome and BAC library sequencing, fine mapping of Me7 markers was performed. The Me7 locus was delimited between two markers G21U3 and G43U3 covering a physical interval of approximately 394.7 kb on the CM334 chromosome P9. Nine markers co-segregated with the Me7 gene. A cluster of 25 putative nucleotide-binding site and leucine-rich repeat (NBS-LRR)-type disease resistance genes were predicted in the delimited Me7 region. We propose that RKN resistance in CM334 is mediated by one or more of these NBS-LRR class R genes. The Me7-linked markers identified here will facilitate marker-assisted selection (MAS) for RKN resistance in pepper breeding programs, as well as functional analysis of Me7 candidate genes in C. annuum.